(3TQM GdMGhj GdUZjQ aj GdaQhYs - (3CHh GddWa eMeO Hf Ydj GHf eGdc GdEQHdi GdTGaYjs; (3fLe GdOjf YHO GdZaGQ Hf YHO GdcQje GdbRhjfj,J (B665 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO Gddg QH GdYGdejf aEf TQGM GdMGhi GdUZjQ bO dgLhG ai JbSje efWhb s
(3BNQgG (B:s
(3hYTQjf UhQI efgG GdJSYhf GdeCNhPI ai efWhbg hCbSGe GdeagheGJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B12s
(3GdfSNI HgG MhGTs
(3hQO ai cTa GdXfhf ai L(B1 (3U` (B625 (3Cf GdMGhi GdUZjQ ai GdaQhY gh deDdaI fLe GdOjf YHO GdZaGQ Hf YHO GdcQje GdbRhjfi GdTGaYi GdeJhai (B665 (3g`s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3MGdI GdfSNI SjFI s
(3GdfSNI HgG CQVg s
Keywords: (3GdeLGejYs